2005
DOI: 10.1159/000087255
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by the Adenosine Derivative IB-MECA in Parental or Multidrug-Resistant HL-60 Leukemia Cells: Possible Relationship to the Effects on Inhibitor of Apoptosis Protein Levels

Abstract: Background: The effects of the A3 adenosine receptor (A3AR) agonist IB-MECA were examined in HL-60 leukemia and in its multidrug-resistant variant HL-60R cells. Methods: Cytotoxicity was evaluated by MTS assays and apoptosis by flow cytometry analyses of DNA fragmentation and phosphatidylserine exposure. The mRNAs of A3AR and inhibitor of apoptosis proteins (IAPs) were determined by RT-PCR. Results: A3AR expression was similar in HL-60 and HL-60R cells. At ≧100 µM, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In addition, our data suggested that P38 MAPK may be involved in A549 cell death. MAP kinases, especially P38 MAPK, have been reported to play important roles in the pathways that regulate both cell cycle and apoptosis 22 . The observation that p38 MAPK facilitates apoptosis through regulation of cell cycle is consistent with these reports 23 …”
Section: Discussionsupporting
confidence: 82%
“…In addition, our data suggested that P38 MAPK may be involved in A549 cell death. MAP kinases, especially P38 MAPK, have been reported to play important roles in the pathways that regulate both cell cycle and apoptosis 22 . The observation that p38 MAPK facilitates apoptosis through regulation of cell cycle is consistent with these reports 23 …”
Section: Discussionsupporting
confidence: 82%
“…Static magnetic field exposure of HL-60 cells increased the increase in [Ca 2+ ] i produced by ATP [457,458]. A 3 receptor agonists were shown to inhibit proliferation and induce apoptosis of HL-60 leukaemia cells [459,460]. ADP and ATP increased [Ca 2+ ] i in CB1 cells, isolated from a patient with T-acute lymphoblastic leukaemia [461], probably via P2Y 1 , P2Y 12 or P2Y 13 receptors.…”
Section: Lymphocytic Leukaemiamentioning
confidence: 99%
“…Recent evidence suggests that apoptosis of cells is closely related to the occurrence, progress and metastasis of tumors [1][2][3] . Study of the mechanisms of apoptosis in tumor cells is an important field of tumor therapy and cancer molecular biology [4][5][6][7] . Adenosine has been shown to induce apoptosis in various systems [8,9] and in the clinical setting, adenosine has also been used to treat some diseases, including arrhythmia.…”
Section: Introductionmentioning
confidence: 99%